Patients Receiving Integrative Medicine Effectiveness Registry (PRIMIER) of the BraveNet practice-based research network: Outcomes of the PRIMIER cohort. (December 2022) - Dusek, Jeffery A.; Gao, Qi; Kim, Ryung S.; Abrams, Donald I.; Kligler, Benjamin; Dyer, Natalie L.; Hansen, Kathryn; McKee, M. Diane; ,
Abstract: Objective: To evaluate the real-world effectiveness of integrative medicine treatment on quality of life using the Patients Receiving Integrative Medicine Effectiveness Registry (PRIMIER). Design: A prospective, longitudinal, observational evaluation of patient reported outcomes for quality of life. Setting: Participants were patients from 17 integrative medicine clinics who received personalized, integrative medicine treatments between August 2013 and October 2017. Main outcome measures: Participants completed the Patient Reported Outcomes Measurement Information System (PROMIS)− 29, Perceived Stress Scale-4 (PSS-4), and the Patient Activation Measure (PAM) at index (baseline) visit and at 2, 4, 6, and 12 month follow-up assessments. Electronic health record data included diagnostic and billing codes/descriptions. A linear mixed-effects model was used to test whether outcomes changed from index through 12 months Results: During enrollment, 4883 participants began the assessment, 3658 completed the index measures, and 2374 (65 %) completed at least 1 follow-up assessment, had electronic health record data and at least 1 integrative medicine visit. Most participants (mean age=51.4 years) were white (88.4 %), female (79.7 %), and college-educated (78.5 %). Significant improvements (p < 0.001) were observed at 12-months on all PROMIS-29 measures, PSS-4, and PAM. At 12 months, clinically meaningful improvements were found for 38 % and 28 % on PROMIS-29 Mental and Physical Health Summary scores respectively. Conclusions: PRIMIER is the largest study to assess the real-world effectiveness of integrative medicine. Results indicate a statistical and clinical improvement across all measures at 12 months. Future research could explore whether dosing, timing or combinations of integrative medicine interventions have differential impacts on quality of life. Highlights: PRIMIER is the largest study to assess the real-world effectiveness of integrative medicine across multiple clinics. Results indicate a statistical and clinical improvement across all measures at 12 months. Future research could explore if dosing or timing of integrative medicine interventions differentially impact outcomes.